A Comparison of Exposure Control Procedures in CATs Using the 3PL Model. (October 2013) - Leroux, Audrey J.; Lopez, Myriam; Hembry, Ian; Dodd, Barbara G.
This study compares the progressive-restricted standard error (PR-SE) exposure control procedure to three commonly used procedures in computerized adaptive testing, the randomesque, Sympson–Hetter (SH), and no exposure control methods. The performance of these four procedures is evaluated using the three-parameter logistic model under the manipulated conditions of item pool size (small vs. large) and stopping rules (fixed-length vs. variable-length). PR-SE provides the advantage of similar constraints to SH, without the need for a preceding simulation study to execute it. Overall for the large and small item banks, the PR-SE method administered almost all of the items from the item pool, whereas the other procedures administered about 52% or less of the large item bank and 80% or less of the small item bank. The PR-SE yielded the smallest amount of item overlap between tests across conditions and administered fewer items on average than SH. PR-SE obtained these results with similar, and acceptable, measurement precision compared to the other exposure control procedures while vastly improving on item pool usage.